2016
DOI: 10.18632/oncotarget.17467
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophil-to-lymphocyte ratio in urothelial carcinoma of the upper urinary tract and bladder: a systematic review and meta-analysis

Abstract: The neutrophil-to-lymphocyte ratio (NLR) is an inflammation marker that has prognostic value for various tumors, but its prognostic value in urothelial carcinoma (UC) remains controversial. This meta-analysis investigated the prognostic value of NLR in UC. A systematic search was performed on PubMed, ISI Web of Science, and Embase for studies focusing on the association between NLR and clinical features or prognosis of UC and published until November 2016. Prognostic outcomes and clinical features were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…Therefore, we assessed the association between the pretreatment NLR and pathological characteristics, and our pooled results demonstrated that the pretreatment NLR could be a significant indicator for lymphovascular invasion (yes vs. no), margin status (positive vs. negative), tumor stage (≥T3 vs. <T3 or T1 vs. Ta) and tumor grade (3 vs. 1, 2). However, no significant association could be found between the pretreatment NLR and concomitant Cis, lymph node involvement, lymph node stage, tumor multifocality or tumor size, which were similar to the pooled results in urothelial carcinoma but differed to some extent [21]. …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Therefore, we assessed the association between the pretreatment NLR and pathological characteristics, and our pooled results demonstrated that the pretreatment NLR could be a significant indicator for lymphovascular invasion (yes vs. no), margin status (positive vs. negative), tumor stage (≥T3 vs. <T3 or T1 vs. Ta) and tumor grade (3 vs. 1, 2). However, no significant association could be found between the pretreatment NLR and concomitant Cis, lymph node involvement, lymph node stage, tumor multifocality or tumor size, which were similar to the pooled results in urothelial carcinoma but differed to some extent [21]. …”
Section: Discussionmentioning
confidence: 52%
“…Previous systematic reviews and meta-analyses have assessed the NLR as a prognostic indicator in upper urinary tract urothelial carcinoma (UUTUC) [20] or urothelial carcinomas [21]. Although UUTUC and urothelial carcinoma of the bladder share many features, they represent two different diseases with varying risk factors, biological behaviors and prognoses [4, 22].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of NLR on patients’ survival time was investigated in some studies [10, 27-30]. The results of a study conducted by Wei et al [10] showed that NLR could be a significant prognostic biomarker in urinary cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In subgroup analyses, high NLR was associated with a worse OS in RCC (HR  1.9, 95% CI 1.47–2.45) and a poor RFS/CSS in RCC (HR   1.83, 95% CI 1.35–2.48), bladder cancer (HR  2.2, 95% CI 1.27–3.8), and urothelial carcinoma (HR  2.58, 95% CI 1.66–4.01) [10]. In another study, increased pretreatment NLR predicted poor OS (HR 1.72, 95% CI 1.45–2.05), PFS (HR 1.68, 95% CI 1.44–1.96), and CSS (HR 1.64, 95% CI 1.39–1.93) in all patients with urothelial carcinoma of the upper urinary tract and bladder [27]. In a group of patients treated at Memorial Sloan Kettering Cancer Center with partial or radical nephrectomy for nonmetastatic clear cell renal carcinoma elevated NLR was significantly associated with worse RFS, CSS, and OS ( p < 0.0001) in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been a large number of studies regarding the prognostic value of NLR in urological cancer, including RCC, UC and PC . In addition, several meta‐analyses showed that increased NLR is associated with worse outcome …”
Section: Differential Blood Cell Markersmentioning
confidence: 99%